(untitled) (Bangladesh Medical Journal Khulna, 2012)
The management of tibial diaphyseal fractures has always held a particular interest for orthopedic surgeons. Not only they are relatively common but also they are often difficult to treat. This prospective study was carried out at Rangpur from April 2008 to November 2009. 34 patients were treated by closed interlocking intramedullary nail. Goal of this study was to find out a safe & effective management of fracture, early mobility of patient, functional joint motion and short stay in hospital. Routine follow up was carried out in 29 patients. In 24 cases, fracture (81.76%) were united, 4 cases (13.79%) needed dynamisation with autogenous bone grafting and 1 case devoloped non union. Study showed interlocking nailing in tibia provides early mobility of patients, reduces hospital stay and fracture unites without joint stiffness and less complication. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10470 Bang Med J (Khulna) 2011: 44(1&2) 15-17